2005
DOI: 10.1007/s10350-005-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-Guided Hemorrhoidal Artery Ligation: An Alternative to Hemorrhoidectomy

Abstract: Doppler-guided ligation of the hemorrhoidal artery is a safe and effective alternative to hemorrhoidectomy and is associated with minimal discomfort and low risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 17 publications
7
43
1
5
Order By: Relevance
“…Regarding items in our study, their results supported our results in group B. (2,(13)(14)(15). In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%).…”
Section: Discussionsupporting
confidence: 80%
“…Regarding items in our study, their results supported our results in group B. (2,(13)(14)(15). In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%).…”
Section: Discussionsupporting
confidence: 80%
“…Different studies have shown that patients with recurrent disease and/or symptoms are suitable candidates for a second DG-HAL [2,5,9]. We initially performed 16 re-DG-HAL procedures.…”
Section: Discussionmentioning
confidence: 99%
“…By combining proctoscopy with a Doppler transducer, it is possible to selectively ligate the vessels in the hemorrhoidal plexus. Multiple studies have shown that Doppler-guided hemorrhoidal artery ligation (DG-HAL) is a safe and easy-to-learn technique with low recurrence rates, and possibly a good alternative to conventional treatments [5,6,7,8,9]. Nevertheless, the rates of effectiveness and patient satisfaction after long-term follow-up are still unknown and, currently, no large, prospective, randomized, controlled trial has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Die nachfolgenden Arbeiten bestätigten die Therapieergebnisse. Jedoch wurden entweder sehr kleine Gruppen von 100 und weniger Patienten analysiert [4,6,8,21], oder die Nachbeobachtungszeit betrug einige Wochen bis maximal 1 Jahr [8,15,21,23]. Die Erfolgraten lagen zwischen 59% [21] und 100% [7], auch im Stadium III.…”
Section: Introductionunclassified